APPLICATION OF A METHOD OF LINEAR CONVOLUTION OF CRITERIA BY OPTIMIZATION OF FINANCIAL SECURITY OF ACTIVITY OF THE ORGANIZATION - A. Zinchenko; I. Bolkvadze; Y. Vnuchkov (Вестник университета)
In article it is proved that problems of financing of activity of the scientific organizations are especially urgent due to the lack at the organizations of necessary level of own current assets and decrease in public financing of scientific activity today. One of alternative forms of financial security are funds of support of science and innovations today. For selection of limited number of projects among the available alternatives by assessment of their importance use of a method of linear convolution of criteria is offered.